Changes in sexual behaviors, network attributes, and STI testing among 15–44-year-olds by marital/cohabiting status and partner number: National Survey of Family Growth, 2008-19 - David A. Katz; Casey E. Copen; Laura T. Haderxhanaj; Matthew Hogben; Deven T. Hamilton (PLoS ONE, 2026)
Background Relationships and recent sexual experience can impact sexual behaviors, networks, and STI testing. How they affect trends in these factors and increasing STI rates is understudied. Methods We analyzed data from 28,027 females and 23,479 males ages 15–44 from the National Survey of Family Growth, 2008–2010 through 2017–2019. We used survey-weighted linear or logistic regression to evaluate linear trends in self-reported sexual behaviors with opposite-sex partners; sexual network attributes; and STI testing, stratified by sex and, separately, by marital/cohabiting status and number of past-year vaginal sex partners (1 vs. ≥ 2). Trends p < 0.050 reported below. Results From 2008–2019, condom use at last vaginal sex decreased among never-married females (51.9% in 2008–10 to 42.9% in 2017–19), never-married males (61.9%−56.3%), and individuals with ≥2 partners (females = 45.3%−34.9%; males = 54.0%−45.7%). Mean number of vaginal sex acts in past 4 weeks decreased among cohabiting females (9.46–7.40), never-married males (4.11–3.40), and males with 1 partner (7.25–6.62). The proportion of never-married females reporting sex with males with male partner(s) increased from 2.5% to 5.1%; similarly, percentages of never-married males (3.8%−5.5%) and males with ≥2 partners (4.6%−6.3%) reporting sex with males increased. Racial/ethnic homophily with current vaginal sex partners decreased among cohabiting females (86.5%−80.4%) and married and never-married males (married = 88.9%−85.9%; never-married = 81.2%−72.3%). Past-year chlamydia testing increased among females who were married (13.0%−17.1%), previously-married (27.6%−45.8%), or had 1 partner (21.7%−25.4%). Conclusions Changes in sexual behaviors, network attributes, and STI testing from 2008–2010 through 2017–2019 varied by marital/cohabiting status and number of past-year opposite-sex partners in complex ways, most commonly among never-married females and males and males with multiple partners. While these changes’ combined potential impact on STI transmission is uncertain, understanding trends in sexual behaviors, networks, and testing by marital/cohabiting status and partner number can contextualize their contributions to the STI epidemic and support sexual health services tailoring and prioritization.